Pengaruh Desain dan Kinerja Elevator terhadap Mobilitas Pengguna di Universitas Matana - Juan Nata; Irene Meylinda Christy (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2019)
Elevators as vertical transportation in multi-storey buildings are a significant part of the circulation in buildings. As a vertical means of transportation, elevators help move each floor of the building user, and directly affect the circulation pattern of the building. Therefore, the availability of good vertical transportation is very influential on the mobility of users in the building. User activities and movements are strongly influenced by circulation patterns and building designs (designation or typology of the building). To find out the effect of design and elevator performance on user mobility at Matana University, quantitative research was conducted by holding questionnaires on 50 respondents at Matana University, then the data was processed with SPSS software to be tested for validity and reliability and tested hypotheses which included correlation test, determination coefficient, significance test, and regression equation. From the research, it was found that there was indeed a strong and significant relationship with rcount = 0.608 and tcount = 5.302 between the design and performance of elevators with user mobility at Matana University, although the influence between these variables was only 36.96%.